Engineered Pseudomonas aeruginosa phages with quorum-quenching enzyme or depolymerase for inhibition of biofilm formation - Luo, Xi; Wang, Siyun; Yang, Yongqing; Gao, Ruyue; Yuan, Shengjian; Yu, Jialin; Liu, Dong; Tan, Xin (Frontiers in Microbiology, 2026)
Pseudomonas aeruginosa is a major cause of healthcare-associated infections and a significant threat to global health, primarily due to its ability to form biofilms that protect it from host immune responses and block antibiotic efficacy. While bacteriophages (phages) are emerging as potential antimicrobial agents, their effectiveness is often limited by these bacterial biofilms. This study aimed to enhance the biofilm-disrupting capabilities of phages through genetic engineering. First, we validated the in vitro biofilm-inhibitory effects of two enzymes: the quorum-quenching lactonase (Aiia) and a phage-derived depolymerase (DP). To demonstrate their potential, we then used CRISPR-Cas9 to engineer the P. aeruginosa phage PaGZ-1 to express these biofilm-disrupting genes. The resulting engineered phages demonstrated superior inhibition of biofilm formation compared to the wild-type phage. Notably, the PaGZ-1-Aiia variant showed significant promise in both inhibiting biofilm formation and disrupting established biofilms. Our findings provide a straightforward method for introducing exogenous genes into non-model P. aeruginosa phage genomes, offering a novel and potentially effective strategy for combating drug-resistant, biofilm-forming infections.